Microbial community analysis of different qualities of pickled radishes by Illumina MiSeq sequencing. Issue 2 (28th November 2018) - Tang, Yanyan; Zhou, Xianrong; Huang, Shenglan; Li, Yuzhu; Long, Mou; Zhao, Xin; Suo, Huayi; Zalán, Zsolt; Hegyi, Ferenc; Du, Muying
Abstract: Pickles are a kind of traditional Chinese fermented vegetable product. To detect microorganism differences, we investigated bacterial and fungal communities in pickled radishes with different qualities and from different regions (Chongqing, Sichuan) using an Illumina MiSeq sequencing method. The results showed that bacterial communities in good‐quality Chongqing pickled radishes (sample A1) contained Pediococcus (40.77%), Lactobacillus (38.46%), Marinospirillum (5.46%), Idiomarina (3.10%), Bacillus (2.17%), Halanaerobium (2.05%), and Halomonas (1.25%), and the fungal communities contained Kazachstania (86.9%), Pichia (6.99%), Candida (3.97%), and Millerozyma (1.23%). In the Sichuan pickled radish (sample A2), the bacterial communities included Bacillus (55.35%), Lactococcus (12.10%), Pediococcus (9.02%), Lactobacillus (3.93%), Streptococcus (2.01%), Pseudomonas (1.98%), Bifidobacterium (1.92%), Arcobacter (1.62%), and Geobacillus (1.05%); Kazachstania (98.64%) was the dominant fungal genus. A microbial community analysis established that Marinobacter and Marinilabilia were associated with texture‐softening of the pickled radishes. The discolored pickled radishes that contained the Suttonella genus was not fit to be eaten. Practical applications: To meet the large demand of the market, industrialized pickle companies use large fermentation tank to ferment vegetables. During the fermentation process, the pickles will be deteriorated if the fermentation conditions are not managed well. It will cause food safety problems and great economic losses. The microbial communities of different qualities of pickled radishes were investigated to determine differences among communities using an Illumina MiSeq sequencing method. This study will help improve the quality of pickled radishes and reduce economic losses in pickle manufacturing.